Targeted recombination between homologous chromosomes for precise breeding in tomato - Shdema Filler Hayut (Nature Portfolio, 2017)
Targeted homologous recombination between parental chromosomes could facilitate precision breeding of crop plants. Here, Filler Hayutet al. show that CRISPR-Cas9 can be used to induce DNA double strand breaks in somatic tissue and achieve targeted recombination between homologs at an endogenous locus in tomato.